Photothermal Conversion Material Derived from Used Cigarette Filters for Solar Steam Generation. Issue 18 (13th August 2019) - Sun, Hanxue; Li, Yuanzhen; Zhu, Zhaoqi; Mu, Peng; Wang, Fei; Liang, Weidong; Ma, Chonghua; Li, An
Abstract: Solar steam generation by photothermal materials has recently emerged as a new and feasible approach to effectively harvest solar energy in a variety of applications. This work reports an efficient heat localization material based on the renewable cellulose acetate cigarette filters and a reduced graphene oxide coating (RGO‐CF) as the light‐to‐heat conversion layer for solar steam generation. RGO‐CF possessed an aligned structure with superhydrophilic nature, lower thermal conductivity (0.0733 Wm −1 K −1 ), and broad light adsorption (≈100 %). These characteristics enable rapid water transportation and excellent light‐to‐heat conversion by the resulting RGO‐CF with an energy conversion efficiency of 94 % under stimulated solar illumination (1 kW m −2 ), which demonstrates that RGO‐CF is a promising photothermal conversion material for solar steam generation. Such strategy for preparation of photothermal materials not only reduces the fabrication cost but also provides a fundamental guidance for the practical application of renewable polymer resources from used cigarette filters. Abstract : Stubs for sustainability ! Renewable cellulose acetate cigarette filters are used to develop an efficient heat localization material for solar steam generation. The proposed methodology provides a guidline for the practical application of renewable polymer resources from used cigarette filters.